Water Resources of Kalmykia: The Contemporary Aspect - SANGADZHIEV, Mergen M.; ONKAEV, Victor A.; BADRUDINOVA, Amina N.; GERMASHEVA, Yuliya S.; ONKAEV, Adik V. (Journal of Environmental Management and Tourism, 2018)
The article analyzes the current state of surface and groundwater resources in the Western Caspian region, Kalmykia. Geological and geographic characteristics of the investigated region are considered: tectonics and stratigraphy, the influence of relief, meandering processes, wells and springs, river and lake shorelines, reservoirs and canals, tailings, origin of desertification foci, climate. The work uses the data of the conducted expedition routes for recent years, the results of reports of state departmental bodies working in the field of ecology. Stock materials of geological organizations and the work of the students of the Faculty of Engineering and Technology of the Kalmyk State University were also used in the article. According to the results of the research, the current state of water resources in Kalmykia, their shortages for drinking needs and the large mineralization that directly affects the growth and development of flora, fauna, desertification and the health of the population of the republic are determined. Particular attention is paid to the issue of water purification and storage and the role of water influence on nutrition and health of the republic's population. The article can also be used by students, researchers to write final qualification papers.